Evaluasi program penguatan pendidikan karakter di SD Muhammadiyah Pakel Plus Yogyakarta - Jadid, Sultan; Widodo, Hendro (Jurnal Pendidikan Karakter, 2023)
This study aims to evaluate the implementation of the character education strengthening program in Pakel Plus Muhammadiyah Elementary School. This type of research is an evaluative research with the CIPP model. Data collection techniques were carried out by interview, observation, and documentation methods. The research subjects consisted of the principal, the KDP program coordinator, 2 classroom teachers, and 3 students. The results showed that the context components of the school's vision, mission, and goals were very appropriate or 80%. The input components, namely HR are very appropriate or 90%; facilities and infrastructure are very appropriate or 90%; as well as appropriate funding sources or 75%. Components of the process of strengthening class-based character education, namely the curriculum is very appropriate or 90%; class management is very appropriate or 90%; and appropriate learning methods or 75%; strengthening school culture-based character education, namely the PPK schedule is very appropriate or 90%; school culture is very appropriate or 90% and extracurricular is very appropriate or 90% and strengthening community-based character education is appropriate or 75%. The product component consists of the results of the implementation of the character education strengthening program for students who are very suitable or 90%.